The Effect of the MURDER Learning Model on Primary Students’ Data Literacy and Mathematical Problem-Solving: A Quasi-Experimental Study - Adhi Eka Widiawan; Wiryanto; Idha Novianti; Hadi Amroni (Universitas Negeri Surabaya, 2025)
According to cognitive scripting theory, systematic learning phases can significantly optimize information processing and enhance cognitive retention. Based on this theoretical justification, the Mood-Understand-Recall-Detect-Elaborate-Review (MURDER) model was implemented to address students' low proficiency in data analysis and probability. This study aims to evaluate the influence of the MURDER model on the data literacy and mathematical problem-solving abilities of fourth-grade students. Using a non-equivalent pretest-posttest control group design, the research involved 74 students in Primary Schools Cluster 2, Slahung District. Through purposive sampling, SDN 5 Slahung was designated as the treatment class ( =16) and SDN 3 Slahung as the control class ( =18). The statistical analysis for data literacy revealed a t-value of 2.91, exceeding the t-table value, which indicates a significant difference between the experimental and control groups. In contrast, mathematical problem-solving abilities yielded a t-value of 1.63, falling below the significance threshold. The study concludes that the MURDER model has a significant influence on data literacy both within and between groups. However, its impact on mathematical problem-solving was limited to within-group improvements only. These findings suggest that while cognitive scripting effectively builds literacy, additional logical scaffolding is required to bridge the gap in complex mathematical problem-solving.